Cellulose degradation in Gastrophysa viridula (Coleoptera: Chrysomelidae): functional characterization of two CAZymes belonging to glycoside hydrolase family 45 reveals a novel enzymatic activity. Issue 5 (31st July 2018) - Busch, A.; Kunert, G.; Wielsch, N.; Pauchet, Y.
Abstract: Cellulose is a major component of the primary and secondary cell walls in plants. Cellulose is considered to be the most abundant biopolymer on Earth and represents a large potential source of metabolic energy. Yet, cellulose degradation is rare and mostly restricted to cellulolytic microorganisms. Recently, various metazoans, including leaf beetles, have been found to encode their own cellulases, giving them the ability to degrade cellulose independently of cellulolytic symbionts. Here, we analyzed the cellulosic capacity of the leaf beetle Gastrophysa viridula, which typically feeds on Rumex plants. We identified three putative cellulases member of two glycoside hydrolase (GH) families, namely GH45 and GH9. Using heterologous expression and functional assays, we demonstrated that both GH45 proteins are active enzymes, in contrast to the GH9 protein. One GH45 protein acted on amorphous cellulose as an endo‐β‐1, 4‐glucanase, whereas the other evolved to become an endo‐β‐1, 4‐xyloglucanase. We successfully knocked down the expression of both GH45 genes using RNAi, but no changes in weight gain or mortality were observed compared to control insects. Our data indicated that the breakdown of these polysaccharides in G. viridula may facilitate access to plant cell content, which is rich in nitrogen and simple sugars.